Unprecedented 17‐Residue Peptaibiotics Produced by Marine‐Derived Trichoderma atroviride. Issue 5 (17th May 2013) - Carroux, Angélique; Van Bohemen, Anne‐Isaline; Roullier, Catherine; Robiou du Pont, Thibaut; Vansteelandt, Marieke; Bondon, Arnaud; Zalouk‐Vergnoux, Aurore; Pouchus, Yves François; Ruiz, Nicolas
Abstract In the course of investigations on marine‐derived toxigenic fungi, five strains of Trichoderma atroviride were studied for their production of peptaibiotics. While these five strains were found to produce classical 19‐residue peptaibols, three of them exhibited unusual peptidic sodium‐adduct [M + 2 Na]2+ ion peaks at m/z between 824 and 854. The sequencing of these peptides led to two series of unprecedented 17‐residue peptaibiotics based on the model Ac‐XXX‐Ala‐Ala‐XXX‐XXX‐Gln‐Aib‐Aib‐Aib‐Ala/Ser‐Lxx‐Aib‐Pro‐XXX‐Aib‐Lxx‐[C129]. The C‐terminus of these new peptides was common to all of them, and its elemental formula C5H9N2O2 was established by HR‐MS. It could correspond to the cyclized form of Nδ‐hydroxyornithine which has already been observed at the C‐terminus of various peptidic siderophores. The comparison of the sequences of 17‐ and 19‐residue peptides showed similarities for positions 1–16. This observation seems to indicate a common biosynthesis pathway. Both new 17‐residue peptaibiotics and 19‐residue peptaibols exhibited weak in vitro cytotoxicities against KB cells.